2014
DOI: 10.1121/1.4892791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spectral content on Horii Oral-Nasal Coupling scores in children

Abstract: A miniature accelerometer and microphone can be used to obtain Horii Oral-Nasal Coupling (HONC) scores to objectively measure nasalization of speech. While this instrumentation compares favorably in terms of size and cost relative to other objective measures of nasality, the metric has not been well characterized in children. Furthermore, the measure is known to be affected by vowel loading, as speech loaded with "high" vowels is consistently scored as more nasal than speech loaded with "low" vowels. Filtering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…HONC data were collected during training with a headset microphone (Shure model WH20; Shure, Inc., Niles, IL) and BU Series 21771 accelerometer (Knowles Electronic, Itasca, IL). The accelerometer signal was band-pass filtered from 400-1000 Hz and the microphone was filtered from 25-420 Hz, allowing for utilization of the low-frequency portion of the signals (Thorp et al, 2013;Varghese et al, 2014). The microphone was placed 7 cm from the mouth at a 45°angle.…”
Section: Signals Collectedmentioning
confidence: 99%
See 1 more Smart Citation
“…HONC data were collected during training with a headset microphone (Shure model WH20; Shure, Inc., Niles, IL) and BU Series 21771 accelerometer (Knowles Electronic, Itasca, IL). The accelerometer signal was band-pass filtered from 400-1000 Hz and the microphone was filtered from 25-420 Hz, allowing for utilization of the low-frequency portion of the signals (Thorp et al, 2013;Varghese et al, 2014). The microphone was placed 7 cm from the mouth at a 45°angle.…”
Section: Signals Collectedmentioning
confidence: 99%
“…HONC instrumentation is lightweight, doesn't require bulky hardware, and has low power consumption (Stevens et al, 1975). Furthermore, HONC scores are correlated with experts' perception of nasality (Horii, 1983), and can effectively differentiate between nasalized and nonnasalized speech tokens (Mra et al, 1998;Thorp, Virnik, & Stepp, 2013;Varghese, Mendoza, Braden, & Stepp, 2014). In addition, previous work has shown that the use of HONC scores to differentiate between nasalized and nonnasalized speech tokens produces results comparable to the use of nasalance (Thorp et al, 2013).…”
mentioning
confidence: 99%
“…This ratio correlates with perceived nasality in healthy adults (Laczi, Sussman, Stathopoulos, & Huber, 2005) and children with VPD (Laczi et al, 2005;Redenbaugh & Reich, 1985). Recent work has led to filtered HONC, in which the accelerometer and microphone signals are bandpass filtered, allowing for comparison of HONC values across participants and vowels (Thorp, Virnik, & Stepp, 2013;Varghese, Mendoza, Braden, & Stepp, 2014).…”
mentioning
confidence: 99%